Characteristic differences and reference ranges for mitral, tricuspid, aortic, and pulmonary Doppler velocity waveforms during fetal life. (12th December 2014) - Kurihara, Yasushi; Tachibana, Daisuke; Yanai, Sakika; Kitada, Kohei; Sano, Miho; Wada, Natsuko; Nakagawa, Kayoko; Yamamoto, Hiroko; Hamuro, Akihiro; Nakano, Akemi; Terada, Hiroyuki; Ozaki, Koji; et al.
Abstract Objectives We aimed to construct reference ranges for time intervals of each component of cardiac flow velocity waveforms in normal fetuses, comparing those variables between right and left ventricles. Methods In 359 fetuses at the gestational age of 17–38 weeks, the durations of atrioventricular (AV) valve opening (AVVO), AV valve closure (AVVC), total E‐ (total‐E) and A‐ (total‐A) waves, total ejection time (total‐ET), acceleration time (acc‐E for E‐wave, acc‐A for A‐wave, and acc‐ET for ejection time), and deceleration time (dec‐E for E‐wave, dec‐A for A‐wave, and dec‐ET for ejection time) were studied cross sectionally. Results Both right and left acc‐E showed the strongest correlations with gestational age (r = 0.478 and r = 0.519, respectively). Left AVVO showed a stronger correlation (r = 0.474) than right AVVO (r = 0.282) and, conversely, right AVVC showed a stronger correlation (r = 0.399) than left AVVC (r = 0.195) with gestational age. Significant differences (all P values <0.001) were observed for all right and left parameters other than total‐A and acc‐E. Conclusions Characteristic differences between right and left ventricles were found in the reference ranges, suggesting the developmental properties of the fetal heart. © 2014 John Wiley & Sons, Ltd.